Things fall apart - Achebe, Chinua; Bandele, Biyi (London : Heinemann Educational Publishers ; Penguin books, 2001)
Okonkwo is the greatest wrestler and warrior alive, and his fame spreads throughout West Africa like a bush-fire. But when he accidentally kills a clansman, things begin to fall apart. Then Okonkwo returns from exile to find missionaries and colonial governors have arrived in the village.
Originally published: London : Heinemann, 1958.
ENH
Keywords: Igbo (African people) -- Fiction; Wrestlers -- Nigeria -- Fiction; Men -- Nigeria -- Fiction; Nigeria -- Race relation -- Fiction